N-terminal regions of Mps1 kinase determine functional bifurcation - Araki, Yasuhiro; Gombos, Linda; Migueleti, Suellen P.S.; Sivashanmugam, Lavanya; Antony, Claude; Schiebel, Elmar (The journal of cell biology, 2010)
Mps1 is a conserved kinase that in budding yeast functions in duplication of the spindle pole body (SPB), spindle checkpoint activation, and kinetochore biorientation. The identity of Mps1 targets and the subdomains that convey specificity remain largely unexplored. Using a novel combination of systematic deletion analysis and chemical biology, we identified two regions within the N terminus of Mps1 that are essential for either SPB duplication or kinetochore biorientation. Suppression analysis of the MPS1 mutants defective in SPB duplication and biochemical enrichment of Mps1 identified the essential SPB components Spc29 and the yeast centrin Cdc31 as Mps1 targets in SPB duplication. Our data suggest that phosphorylation of Spc29 by Mps1 in G1/S recruits the Mps2-Bbp1 complex to the newly formed SPB to facilitate its insertion into the nuclear envelope. Mps1 phosphorylation of Cdc31 at the conserved T110 residue controls substrate binding to Kar1 protein. These findings explain the multiple SPB duplication defects of mps1 mutants on a molecular level.